Investigation of Track Superstructure Ballastless Design - A. V. Savin; A. M. Brzhezovskiy; V. V. Tret’Yakov; I. V. Smelyanskiy; S. V. Tolmachev (Вестник Научно-исследовательского института железнодорожного транспорта, 2015)
In 2009 there were constructed and brought into pilot operation two sections of RHEDA 2000 ballastless track designed by RailOne (Germany) with the participation of JSC ‘‘Roszheldorproekt”, one of them on the Moskovskaya Railway (in the VNIIZhT’s Testing Center at the station of Scherbinka) and another - on Oktyabr’skaya Railway (on the open line between Sablino and Kolpino). Prior to and in the course of pilot operation the VNIIZhT experts conducted actual loading tests at both sections and routine observations of various ballastless track components’ behaviour under increasing passed tonnage conditions. There are presented the most significant test and observation results as well as test results based conclusions.